2019
DOI: 10.1111/ejh.13213
|View full text |Cite
|
Sign up to set email alerts
|

Sequential liver and haematopoietic stem cell transplantation in a case of fulminant hepatitis associated liver failure and aplastic anaemia

Abstract: Hepatitis-associated aplastic anaemia (HAAA) is a potentially lethal complication of acute hepatitis where pancytopenia develops a few months after the acute hepatitis episode. As with severe aplastic anaemia (SAA), the pathogenic mechanism is thought to be immune-mediated destruction of haematopoietic stem cells (HSCs) leading to bone marrow failure and pancytopenia. Acute hepatitis may progress to fulminant hepatic failure (FHF) necessitating liver transplantation as a life-saving measure. The optimal manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, FH did not recur after LDLT even though the donor's liver shared the HLA haplotype that was lost in the recipient liver as a result of 6pLOH. Previous studies that reported successful treatment of HAAA after LDLT with IST did not observe a recurrence of FH in the donor's liver either 5,9,10,12–14 . Although the reason for the non‐recurrence of FH in our patient is unclear, the target antigen of pathogenic CD8 + T cells may be a polymorphic protein unique to the recipient.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…On the other hand, FH did not recur after LDLT even though the donor's liver shared the HLA haplotype that was lost in the recipient liver as a result of 6pLOH. Previous studies that reported successful treatment of HAAA after LDLT with IST did not observe a recurrence of FH in the donor's liver either 5,9,10,12–14 . Although the reason for the non‐recurrence of FH in our patient is unclear, the target antigen of pathogenic CD8 + T cells may be a polymorphic protein unique to the recipient.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies that reported successful treatment of HAAA after LDLT with IST did not observe a recurrence of FH in the donor's liver either. 5,9,10,[12][13][14] Although the reason for the non-recurrence of FH in our patient is unclear, the target antigen of pathogenic CD8 + T cells may be a polymorphic protein unique to the recipient.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The cause of hepatitis appears to be an undetermined virus, and the underlying pathological mechanism may be immune-mediated 1 . Several cases of HAAA have been successfully treated by allogeneic hematopoietic stem cell transplantation (HSCT) or immunosuppressive treatment [2][3][4] . However, HSCT is not feasible for all patients.…”
Section: Introductionmentioning
confidence: 99%